C/N/O centred metal clusters: super valence bonding and magic structure with 26 valence electrons. (3rd March 2020) - Tang, Jianling; Zhang, Cairong; Chen, Hongshan
Abstract : By using genetic algorithm combined with B3LYP and QCISD methods, this paper investigates the stabilities and electronic structures of Al6 OM m (M = Na, K; m = 2, 4, 6) and a few other Al n XNa m (X = C, N, O) clusters. The results show that the nonmetal doped metal clusters with 26 valence electrons have enhanced stabilities and large energy gaps. This paper extends the Jellium model for the application to the nonmetal doped metal clusters and explains the electronic origin of this strong magic structure. The nonmetal X atom is situated in the centre of the magic clusters. The 2s/2p orbitals of the central atom interact strongly with the superatomic 1S/1P orbitals and form bonding and antibonding orbitals. The bonding orbitals make the C/N/O atoms form s 2 p 6 shell closure, and the antibonding orbitals make the metal moieties form closed 2S 2 2P 6 shells. The 26 valence electrons form closed s 2 p 6 S 2 P 6 D 10 shells, and this electronic configuration can be taken as the combination of the octet rule and 18-electron rule. The octahedral Al6 O 2− core is a superatomic anion with great stability, and it can be used as building blocks to assemble Zintl phase materials by interaction with alkali metals. GRAPHICAL ABSTRACT: UF0001